Ribosomal S6 Kinase Regulates the Timing and Entrainment of the Mammalian Circadian Clock Located in the Suprachiasmatic Nucleus. (15th April 2023) - Hoyt, Kari R.; Li, Aiqing; Yoon, Hyojung; Weisenseel, Zachary; Watkins, Jacob; Fischer, Alex; Obrietan, Karl
Highlights: The three ERK-regulated RSK isoforms (RSK1-3) are expressed in the SCN. Photic stimulation triggers RSK/ERK dissociation and RSK nuclear translocation. RSK couples light to SCN clock entrainment. RSK inhibition slows the period of the SCN oscillator. Abstract: Previous work in the suprachiasmatic nucleus (SCN), the locus of the principal circadian clock, has shown that the activation state of the ERK/MAPK effector p90 ribosomal S6 kinase (RSK) is responsive to photic stimulation and is modulated across the circadian cycle. These data raise the prospect that RSK signaling contributes to both SCN clock timing and entrainment. Here, we found marked expression of the three main RSK isoforms (RSK1/2/3) within the SCN of C57/Bl6 mice. Further, using a combination of immunolabeling and proximity ligation assays, we show that photic stimulation led to the dissociation of RSK from ERK and the translocation of RSK from the cytoplasm to the nucleus. To test for RSK functionality following light treatment, animals received an intraventricular infusion of the selective RSK inhibitor, SL0101, 30 min prior to light (100 lux) exposure during the early circadian night (circadian time 15). Notably, the disruption of RSK signaling led to a significant reduction (∼45 min) in the phase delaying effects of light, relative to vehicle-infused mice. To test the potential contribution of RSK signaling to SCN pacemaker activity, slice cultures from a per1 -Venus circadian reporter mouse line were chronically treated with SL0101. Suppression of RSK signaling led to a significant lengthening of the circadian period (∼40 min), relative to vehicle-treated slices. Together, these data reveal that RSK functions as a signaling intermediate that regulates light-evoked clock entrainment and the inherent time keeping properties of the SCN.